Computer simulation of body motion under the action of Central attraction - Ахатаева , Ж.; Шакерхан , К.; Керимбаев , А.; Мукушев , Б. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article analyzes natural and virtual Central forces. There are presented results of the study of body motion in the field of these forces are presented. These results were obtained through computer experiments. Possible orbits of a body’s motion in the field of Central forces of gravitational (or Coulomb) and quasi-elastic nature are studied on the basis of Bertrand’s theorem. Authors consider virtual Central forces. The study of these forces is of great scientific value in the methodology of physical science. The study of natural and virtual forces was carried out using computer modeling. Computer programs were compiled using the Mathcad application package. Using the Mathcad package, the trajectories of the body in the field of various Central forces were determined. The results of the conducted computational experiment was to prove the theorem of Bertrand. Under certain initial conditions, a body can move along a closed trajectory in two cases: in the field of gravitational force and in the field of quasi-elastic force. In both cases, the body moves along the path of an ellipse, circle, parabola, and hyperbola. When computer modeling the motion of bodies in the field of virtual forces, different trajectories were obtained depending on the initial conditions.